Воздействие лазерного и ВЧ-излучений на воздушную среду: Монография - Копытин Ю. Д; Протасевич Е. Т; Чистякова Л. К; Шишковский В. И; Землянов А. А (Новосибирск, Наука, 1992)
Авт. указаны на обороте тит. листа